An An Error Analysis on The Use of Adverbs 就 (Jiù) and 才 (Cái) in Class XI IPS 5 Students of SMA NEGERI 6 Malang - Amalya Hasky Dwi Mahayu; Desti Nur Aini; Lukluk Ul Muyassaroh (Journal of Chinese Language and Culture Studies, 2025)
Learning and mastering multiple languages is very useful for future careers, including learning Mandarin. This is because China is an economically superior country that has a major impact on the global economy, including Indonesia. Many large companies in Indonesia have business relations with China so large companies currently need workers who can speak Mandarin. This research aims to describe the mistakes in using adverbs 就, to describe the mistakes in using adverbs 才, and to describe the factors that cause mistakes in using adverbs 就 and 才 in a sentence. This study uses a qualitative descriptive research method. The researcher found several mistakes made by students when carrying out student performance tests, besides that the researcher also found several factors that caused students to make mistakes in using the adverbs jiù and cái. So the researcher is interested in conducting a study entitled "Analysis of Errors in the Use of Adverbs 就 (jiù) and 才 (cái) in Class XI IPS 5 Students of SMA Negeri 6 Malang".